Indications for CBCT examination in pediatric patients: a cross-sectional study - Arisandy, Marini; Wulansari, Dwi Putri; Rahman, Fadhlil Ulum Abdul (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: This study aims to portray the characteristic of cone beam computed tomography (CBCT) indication on pediatric patients based on age, gender, specialist field, clinical indications, and radiation doses. Materials and Methods: CBCT images of 55 pediatric patients were investigated retrospectively. CBCT images were obtained with three categories field of view (FOV). CBCT indications were categorized as dental anomalies, impacted teeth, orofacial cleft, orthodontic needs, endodontics, osseous pathological lesion, dentoalveolar trauma, and temporo mandibular disorder. The effect of age, sex, and FOV were evaluated. Results: The most common indication for using CBCT is impacted teeth (45%), osseous pathological lesion (17%), and dentoalveolar trauma (11%). There were not significant association between sex, age group, and FOV to CBCT indication. Conclusion: CBCT examination at Dental Hospital of Hasanuddin University is needed in pediatric patients mainly to diagnose oral pathology, impacted teeth, and dentoalveolar trauma. Determining CBCT for pediatric patients should be indicative-oriented suitably with as low as diagnotically achievable being indication-oriented and patient-specific (ALADAIP) principles.